www.5129.net > (x+6)÷4=2.6解方程

(x+6)÷4=2.6解方程

(x+6)÷4=2.6解方程 x+6=4×2.6 x+6=10.4 x=10.4-6 x=4.4

2x-8=12-6x,8x=20,x= 5 2 .

(x+2)÷4等于6.5解方程 解 (x+2)÷4=6.5 x+2=6.5×4 x+2=27 x=25

(x×5/12+6)÷(x+6)=1/2, (5/12)x+6=(1/2)(x+6), 5x+72=6(x+6), 5x+72=6x+36, x=36

2x(x+1)=6 x+1=6÷2 x+1=3 x=3-1 x=2

x=13×2.6

x(x-1)=12 x^2-x-12=0 (x-4)(x+3)=0 所以 x1=4 x2=-3

(1)x2+x6=4 23x=4 23x÷23=4÷23 x=6;(2)x+x4=20 114x=20114x÷114=20÷114 x=16.

x*6=(38.4/2-x)*10 6x+10x=5*38.4 16x=192 x=12

(x-2.6)÷0.7=2.8 解:x-2.6=2.8*0.7 x-2.6=1.96 x=4.56

网站地图

All rights reserved Powered by www.5129.net

copyright ©right 2010-2021。
www.5129.net内容来自网络,如有侵犯请联系客服。zhit325@qq.com